Retrograde ejaculation after holmium laser enucleation of the prostate (HoLEP)—Impact on sexual function and evaluation of patient bother using validated questionnaires. (31st August 2020) - Gild, Philipp; Dahlem, Roland; Pompe, Raisa S.; Soave, Armin; Vetterlein, Malte W.; Ludwig, Tim A.; Maurer, Valentin; Marks, Phillip; Ahyai, Sascha A.; Chun, Felix K.‐H.; Lenke, Lukas; Ernst, Tabea; et al.
Abstract: Background: A vast body of literature has focused on erectile function after Holmium Laser Enucleation of the Prostate (HoLEP). Interestingly, retrograde ejaculation (RE), despite its frequency has sparsely been investigated. Objectives: To study patient perception and impact of RE on sexuality following HoLEP. Materials and methods: We retrospectively analyzed 2, 131 patients undergoing HoLEP 2006‐2015 at our institution. Patients were followed via standardized questionnaires namely International Index of Erectile Function (IIEF) as well as Male Sexual Health Questionnaire Ejaculatory Short Form (MSHQ‐EjD‐SF). Exclusion criteria were missing/follow‐up <6 months, missing data on MSHQ‐EjD‐SF and IIEF score, resulting in 535 assessable patients. Multivariable logistic regression was employed to identify independent predictors of satisfaction with overall sex life (IIEF question 13). Results: Median follow‐up was 50 months (IQR: 30‐78). Overall, 495 (92.5%) patients reported RE. Patients differed significantly with respect to age ( P = .036), IPSS at follow‐up ( P = .01), and erectile function ( P < .001), whereas no other statistically significant differences were observed. In multivariable logistic regression analyses, presence of RE was not independently associated with satisfaction with overall sex life (OR: 2.7, 95% CI: 0.70‐10.5, P = .1). However, in the cohort of patients exhibiting RE, patients who stated "feeling bothered by RE" had lower satisfaction with overall sex life (OR: 0.23, 95% CI: 0.13‐0.38, P < .001). Bother by RE varied according to erectile function and did not impact overall satisfaction in men with superior erectile function. Conclusions: RE is a very common event after HoLEP but in this retrospective analysis was not associated with overall satisfaction with sex life. Contrary, satisfaction with sex life is impaired in patients who feel bothered by RE. Proper patient selection will pose key to identify patients in which RE bother will offset the benefits of LUTS relief.